The Effect of Edmodo in Triggering Students’ Recognition of Recount Text Elements - M. Fadhly Farhy Abbas; Siti Sahnia Mammenasa Daeng Yusuf (Lectura : Jurnal Pendidikan, 2020)
The difficulty of students writing recount was found at MTs Hasanah Pekanbaru. The students could not write good recount text because of lack of vocabulary and lack of knowledge about recount text. In addition, the students hope that the use of technology in teaching because the strategy is not interesting enough that makes creativity low in writing. Knowing the effects of using Edmodo on learning English that can help the teacher to present the materials and help the students to find and develop the ideas and into elements of recount text at the eighth grade of MTs Hasanah Pekanbaru. This research was a quasi-experimental research. The sample was two classes VIII.4 with 26 students and VIII.5 with 24 students. After conducting this research using Edmodo, the results of the post-test scores of the experimental class were higher than the pre-test scores that were with less effective level. This can be seen from the average post-test score of the experimental class was 52.83, and it was increased from the pre-test score was 30.63 with a gain of 22.2 and N-gain 0.31. The average post-test on the control was 33.69, and it was lower than the experimental class with the gain 8.1 and N-gain 0.1. As the conclusion, there was a significance effect of the students who received in class experimental using Edmodo than the students who did not received classroom instruction using Edmodo in recognizing a recount text.